Analisis Kebutuhan dan Ketersediaan Air Baku Pemanfaatan Bendungan Ameroro Kabupaten Konawe - Kiki Iqrayanti (Jurnal Proyek Teknik Sipil, 2026)
The availability of clean water is a basic necessity that must be sustainably fulfilled in line with population growth and regional development. Konawe Regency has significant water resource potential, one of which is the Ameroro Dam, which is planned as a raw water supply source with a capacity of 511 liters per second. This study aims to analyze the demand and availability of raw water from the Ameroro Dam in meeting clean water needs in the planned service area covering ten sub-districts up to the year 2044. The analysis results indicate that the population in the study area increased from 134,078 people in 2024 to 154,581 people in 2044. The peak-hour clean water demand in 2044 is estimated at 509.302 liters per second. A comparison between water demand and raw water availability shows that the capacity of the Ameroro Dam is still sufficient to meet the clean water needs of the planned service area until the end of the planning period. The findings of this study are expected to serve as a basis for planning, development, and sustainable management of clean water supply systems in Konawe Regency.